2002
DOI: 10.1111/j.1752-1688.2002.tb01544.x
|View full text |Cite
|
Sign up to set email alerts
|

FLOOD STAGE FORECASTING WITH SUPPORT VECTOR MACHINES1

Abstract: Machine learning techniques are finding more and more applications in the field of forecasting. A novel regression technique, called Support Vector Machine (SVM), based on the statistical learning theory is explored in this study. SVM is based on the principle of Structural Risk Minimization as opposed to the principle of Empirical Risk Minimization espoused by conventional regression techniques. The flood data at Dhaka, Bangladesh, are used in this study to demonstrate the forecasting capabilities of SVM. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
143
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(150 citation statements)
references
References 14 publications
2
143
0
Order By: Relevance
“…Han et al (2007) compared the RBF and linear kernel functions and found that even within the same catchment, the ideal function can change under different circumstances. Despite being a relatively new approach to hydrological modelling, SVMs and SVRs have been applied to many of the same problems as ANNs, including rainfallrunoff modelling for water resources planning and flood forecasting at various lead-times (Asefa et al, 2006;Han et al, 2007;Behzad et al, 2009;Rasouli et al, 2012), hydraulic modelling (Liong and Sivapragasam, 2002) and downscaling of GCM output (Tripathi et al, 2006). Genetic Programming (GP; Koza, 1992) is another soft computing approach to non-linear modelling and is based on Darwin's theory of evolution by natural selection.…”
Section: Approaches To Hydrological Modellingmentioning
confidence: 99%
“…Han et al (2007) compared the RBF and linear kernel functions and found that even within the same catchment, the ideal function can change under different circumstances. Despite being a relatively new approach to hydrological modelling, SVMs and SVRs have been applied to many of the same problems as ANNs, including rainfallrunoff modelling for water resources planning and flood forecasting at various lead-times (Asefa et al, 2006;Han et al, 2007;Behzad et al, 2009;Rasouli et al, 2012), hydraulic modelling (Liong and Sivapragasam, 2002) and downscaling of GCM output (Tripathi et al, 2006). Genetic Programming (GP; Koza, 1992) is another soft computing approach to non-linear modelling and is based on Darwin's theory of evolution by natural selection.…”
Section: Approaches To Hydrological Modellingmentioning
confidence: 99%
“…However, along with the introduction of Vapnik's ε insensitive loss function, SVMs have been extended to solve nonlinear regression estimation (Gunn, 1998;Smola & Schölkopf, 2004) and time series forecasting (Thissen et al, 2003). It is useful to note that the SVM is finding its way into the water sector (Liong & Sivapragasm, 2002;Bray & Han, 2004;Asefa et al, 2004) and a combination of SVM and evolutionary algorithm called EC-SVM has also been attempted recently (Yu et al, 2004). In the latter study, a shuffled complex evolution (SCE-UA) algorithm (Duan et al, 1992(Duan et al, , 1993(Duan et al, , 1994 was used to search phase space parameters (the time delay embedding dimension) and three SVM parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to build an adequate direct prediction model that learnt a response function of the given system. To evaluate the stability of the recursive model building, the RP-DP ratio [24] was calculated for T-R-F and T-R-G-F type models with 216 candidate model parameter groups: prediction direct the of RMSE prediction recursive the of RMSE ratio DP RP = − (17) The RP-DP ratio value stands for the extent of the consistency between the direct and recursive prediction models. Thus, a narrower distribution with lower values of the RP-DP ratio indicates a higher possibility that a recursive prediction model of high consistency with a direct prediction model is selected.…”
Section: Recursive Prediction Of Fslmentioning
confidence: 99%
“…Recently, in the field of hydrology and hydrogeology, research on the application of time series models-based on machine learning techniques such as an artificial neural network (ANN) and a support vector machine (SVM) to prediction of water resources variations-have been increased; Zealand et al [11] utilized the ANN for forecasting short term stream flow of the Winnipeg River system in Canada; Akhtar et al [12] applied ANN to river flow forecasting at Ganges river; Hu et al [13] explored new measures for improving the generalization ability of the ANN for the prediction of the rainfall-runoff; Coulibaly et al [14] and Mohanty et al [15] examined the performance of ANN for the prediction of groundwater level (GWL) fluctuations; Coppola et al [16] used the ANN for the prediction of GWL under variable pumping conditions; Liong and Sivapragasam [17], and Yu et al [18] employed the SVM for the prediction of the flood stage; Asefa et al [19] used the SVM for designing GWL monitoring networks; Gill et al [20] assessed the effect of missing data on the performance of ANN and SVM models for GWL prediction; Yoon et al [21] used ANN and SVM for long-term GWL forecast.…”
Section: Introductionmentioning
confidence: 99%